Memorial days ebook A memoir. - Brooks, Geraldine (2025)
A New York Times Bestseller “Brooks tracks the geography of grief with patience and grace as she comes to terms with the ongoing nature of outliving the ones you love most. ... Her memoir is certainly a testament to her own unique loss, but it’s moreover a lifeline to others who will find themselves in this familiar, shattered landscape of grief.” — Los Angeles Times “A rich account of marriage and mourning.” — Washington Post A heartrending and beautiful memoir of sudden loss and a journey towards peace, from the bestselling, Pulitzer Prize-winning author of  Horse Many cultural and religious traditions expect those who are grieving to step away from the world. In contemporary life, we are more often met with red tape and to-do lists. This is exactly what happened to Geraldine Brooks when her partner of more than three decades, Tony Horwitz – just sixty years old and, to her knowledge, vigorous and healthy – collapsed and died on a Washington, D. C. sidewalk. After spending their early years together in conflict zones as foreign correspondents, Geraldine and Tony settled down to raise two boys on Martha’s Vineyard. The life they built was one of meaningful work, good humor, and tenderness, as they spent their days writing and their evenings cooking family dinners or watching the sun set with friends at the beach. But all of this ended abruptly when, on Memorial Day 2019, Geraldine received the phone call we all dread. The demands were immediate and many. Without space to grieve, the sudden loss became a yawning gulf. Three years later, she booked a flight to a remote island off the coast of Australia with the intention of finally giving herself the time to mourn. In a shack on a pristine, rugged coast she often went days without seeing another person. There, she pondered the various ways in which cultures grieve and what rituals of her own might help to rebuild a life around the void of Tony’s death. A spare and profoundly moving memoir that joins the classics of the genre, Memorial Days is a portrait of a larger-than-life man and a timeless love between souls that exquisitely captures the joy, agony, and mystery of life.